2012
DOI: 10.1248/bpb.b12-00352
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol-Induced Apoptosis in HCT-116 Colon Cancer Cells Is Associated with the AMP-Activated Protein Kinase Signaling Pathway

Abstract: Colon cancer is the third most common malignancy around the world. Surgery, chemotherapy, and radiotherapy are generally used to treat colon cancer, but no effective therapy for advanced colon carcinoma is available. Therefore, there is a need to identify other therapeutic agents against this disease. Magnolol, a hydroxylated biphenyl compound present in Magnolia officinalis, exerts anticancer potential and low toxicity. Emerging evidence has suggested that activation of AMP-activated protein kinase (AMPK), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…This results of the study have shown that magnolol 2 downregulated expression of the antiapoptotic protein Bcl-2, upregulated expression of pro-apoptotic protein p53 and Bax, and caused the release of mitochondrial cytochrome c. Magnolol 2 induced p53 and Bcl-2 expression was abolished in the presence of magnolol compound. Magnolol inhibited migration and invasion of HCT-116 cells through AMPK activation [24]. These findings demonstrate that AMPK mediates the anticancer effects of magnolol through apoptosis in HCT-116 cells.…”
Section: Fadilah Et Alsupporting
confidence: 51%
“…This results of the study have shown that magnolol 2 downregulated expression of the antiapoptotic protein Bcl-2, upregulated expression of pro-apoptotic protein p53 and Bax, and caused the release of mitochondrial cytochrome c. Magnolol 2 induced p53 and Bcl-2 expression was abolished in the presence of magnolol compound. Magnolol inhibited migration and invasion of HCT-116 cells through AMPK activation [24]. These findings demonstrate that AMPK mediates the anticancer effects of magnolol through apoptosis in HCT-116 cells.…”
Section: Fadilah Et Alsupporting
confidence: 51%
“…Interestingly, MAG treatment with colon cancer induced apoptosis by upregulating the expression of the p27Cip1 protein [133]. Park J.B. et al, reported that HCT-116 colon cancer cells upon treatment with MAG activated AMP-activated protein kinase (AMPK), enhanced the expression of pro-apoptotic protein Bax and p53 and downregulated the anti-apoptotic protein Bcl-2 [132]. Another study conducted by Kang Y.J.…”
Section: Effect Of Magnolol In Different Cancersmentioning
confidence: 99%
“…Another group of polyphenols of interest are lignans and particularly, magnolol (Table 1), a compound isolated from roots and barks of Magnolia officinalis that has recently shown interesting anticancer activity through AMPK modulation [31,32,33]. The treatment of HCT-116 human colon cancer cells with this compound induced apoptosis and exerted anti-proliferative effects in a dose and time dependent manner.…”
Section: Nutraceutical Compounds and Cancermentioning
confidence: 99%